KERUGIAN KONTRAKTOR AKIBAT WASTE MATERIAL PROYEK KONSTRUKSI GEDUNG BERTINGKAT - Hendrik Sulistio; Mega Waty (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
Waste in the construction sector can be interpreted as loss or loss of various resources, namely material, time (related to labor and equipment), and capital, which is caused by activities that require direct or indirect costs but do not add value to the final product for service users This study was conducted on 64 respondents of building construction projects to determine the magnitude of losses due to ready mix concrete and its causes. Research using a questionnaire distributed through the online system. Of the 64 respondents produced 9.06 % which is the loss of ready mix concrete. The loss of Ready Mix concrete is 9.06% of the profit of Ready Mix Concrete. The validity test and reliability test produced 18 causative factors that caused the loss of ready mix concrete material waste. The biggest factors causing the loss of ready mix concrete are: lost due to being stolen, design changes, detailed drawing details and material orders that are not according to specifications and scattered when transported/moved.